(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The alien fraction of the Mykolayiv urban flora includes 235 species, which are composed 25.8% of the total species number of the studied flora. Geographic range 28 groups are combined in eight migroelements of the flora. They are: Mediterranean migroelement – 48 species, Mediterranean Irano-Turanian – 42, North American – 37. Four species are of anthropogenic origin. Primary areas of distribution were not considered for five species. All alien species are distributed between three migrochronoelements by their period of immigration. They are archeophytes (immigrated before the 15th century) – 77 species, kenophytes (immigrated during the 16 – 19th centuries) – 69, and eukenophytes (immigrated in the 20th century) – 89.